Активирование процесса спекания железных порошков путем введения нанодисперсных добавок - Матренин С. В. Сергей Вениаминович; Ильин А. П. Александр Петрович; Слосман А. И. Аркадий Иосифович; Толбанова Л. О. Людмила Олеговна (2009, 2009)
Заглавие с экрана